Experiences from treating seven adult 5q spinal muscular atrophy patients with Nusinersen - Elisabeth Jochmann; Robert Steinbach; Thomas Jochmann; Ha-Yeun Chung; Annekathrin Rödiger; Rotraud Neumann; Thomas E. Mayer; Klaus Kirchhof; Dana Loudovici-Krug; Ulrich C. Smolenski; Otto W. Witte; Julian Grosskreutz (Therapeutic Advances in Neurological Disorders, 2020)
Background: The antisense oligonucleotide Nusinersen recently became the first approved drug against spinal muscular atrophy (SMA). It was approved for all ages, albeit the clinical trials were conducted exclusively on children. Hence, clinical data on adults being treated with Nusinersen is scarce. In this case series, we report on drug application, organizational demands, and preliminary effects during the first 10 months of treatment with Nusinersen in seven adult patients. Methods: All patients received intrathecal injections with Nusinersen. In cases with severe spinal deformities, we performed computed tomography (CT)-guided applications. We conducted a total of 40 administrations of Nusinersen. We evaluated the patients with motor, pulmonary, and laboratory assessments, and tracked patient-reported outcome. Results: Intrathecal administration of Nusinersen was successful in most patients, even though access to the lumbar intrathecal space in adults with SMA is often challenging. No severe adverse events occurred. Six of the seven patients reported stabilization of motor function or reduction in symptom severity. The changes in the assessed scores did not reach a significant level within this short time period. Conclusions: Treating adult SMA patients with Nusinersen is feasible and most patients consider it beneficial. It demands a complex organizational and interdisciplinary effort. Due to the slowly decreasing motor functions in adult SMA patients, long observation phases for this recently approved treatment are needed to allow conclusions about effectiveness of Nusinersen in adults.